2009
DOI: 10.1165/rcmb.2008-0358oc
|View full text |Cite
|
Sign up to set email alerts
|

Airway Epithelium Stimulates Smooth Muscle Proliferation

Abstract: Communication between the airway epithelium and stroma is evident during embryogenesis, and both epithelial shedding and increased smooth muscle proliferation are features of airway remodeling. Hence, we hypothesized that after injury the airway epithelium could modulate airway smooth muscle proliferation. Fully differentiated primary normal human bronchial epithelial (NHBE) cells at an air-liquid interface were co-cultured with serum-deprived normal primary human airway smooth muscle cells (HASM) using commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 60 publications
3
66
1
Order By: Relevance
“…Beklen et al (7) showed that there was an upregulation of both MMP9 and IL-8 in periodontitis. Many studies related with airway epithelium have shown a direct link between the IL-8 secretion and MMP9 expression (15,31,55). Yoon et al (55) have shown that MMP9 protects from ozone induced airway injury may be via posttranscriptional effects on IL-8.…”
Section: Discussionmentioning
confidence: 99%
“…Beklen et al (7) showed that there was an upregulation of both MMP9 and IL-8 in periodontitis. Many studies related with airway epithelium have shown a direct link between the IL-8 secretion and MMP9 expression (15,31,55). Yoon et al (55) have shown that MMP9 protects from ozone induced airway injury may be via posttranscriptional effects on IL-8.…”
Section: Discussionmentioning
confidence: 99%
“…To date, relatively little attention has been paid to modeling at the cellular or subcellular level in the lung, or to in response to epithelial challenges including physical damage (Malavia et al, 2009;Thompson et al, 2006), viral infection (Tomei et al, 2008) or mechanical strain to simulate the effect of bronchoconstriction on the epithelium (Choe et al, 2003). Similarly, by co-culturing airway epithelial and endothelial cells, it has been shown that cell-cell communication involving soluble endothelial-derived factor(s) causes a significant reduction in paracellular permeability compared to that seen when epithelial or endothelial monolayers are studied in monoculture (Chowdhury et al, 2010).…”
Section: In Silico Modelingmentioning
confidence: 99%
“…Silencing of MMP-9 abrogates the epithelium-dependent increase in BSM cell proliferation. Finally, epithelial injury increases the release of MMP-9 and the expression of Ki67 levels in human BSM cells [157], suggesting that epithelium and BSM strongly interact in asthma.…”
Section: Migration Of Myofibroblastsmentioning
confidence: 96%
“…In addition, corticosteroids do not prevent TGF-b-induced EMT but decrease it [156]. Furthermore, bronchial epithelium modulates BSM cell proliferation through an IL-6 and MMP-9-dependent mechanism [157]. Silencing of MMP-9 abrogates the epithelium-dependent increase in BSM cell proliferation.…”
Section: Migration Of Myofibroblastsmentioning
confidence: 97%